33‐5: Fabrication Paths of Liquid‐Crystal Photonics for AR/VR Optical Systems. Issue 1 (28th June 2021) - Wang, Mengfei; Lu, Lu; Curts, Kyle; Choi, Stephen; Tu, Xingzhou; Lee, Yun-Han; Wang, Junren; Silverstein, Barry
Abstract : In this paper, we discuss different photo‐patterning paths for fabricating liquid crystal photonics devices, like geometric phase elements and polarization volume holograms for augmented reality and virtual reality (AR/VR) optical systems. We review the viability of typical photo‐patterning methods for small‐quantity research purposes, with a focus on direct write and interference recording. We present detailed comparisons between direct duplication and projection duplication, with recommendations for cost‐ and time‐efficient manufacturing paths.